Application of plow-tillage as an innovative technique for eliminating overwintering cyanobacteria in eutrophic lake sediments. (December 2016) - Zhou, Qilin; Liu, Cheng; Fan, Chengxin
Abstract: Surface sediment in eutrophic lakes is both a destination and a habitat for overwintering cyanobacteria. The resuspension and recovery of viable, overwintering cyanobacteria from the surface sediment during warm spring weather is usually the primary stage of cyanobacterial blooms (CBs) in shallow eutrophic lakes. Therefore, the elimination of overwintering cyanobacteria in sediment is vital to control CBs. In the present study, sediment plow-tillage (PT) was introduced as an innovative technique for eliminating overwintering cyanobacteria in sediments from Lake Chaohu. Four depths of PT (2, 5, 10, and 15 cm) were tested during the 42-day experiment. The results showed that rapid cell death during the first 0–7 d after PT was accompanied by high oxygen uptake rates. The viable cells in deeper sediment died more quickly and at a higher rate after PT. A PT depth of >10 cm effectively eliminated viable cyanobacteria (with a removal rate of 82.8%) from the sediment and prevented their resuspension. The activity of the viable cyanobacteria also decreased quickly as cyanobacteria were eliminated. It appears that the dark, anoxic environment of the deeper sediment after PT was responsible for the elimination of viable cells. Although high release rates of nitrogen and phosphorus were found to accompany the dying and decomposition of cyanobacteria during days 0–7 of the experiment, greater depth of PT was found to decrease nutrient concentrations in the overlying water. In conclusion, we recommend sediment PT as a new technique for eliminating overwintering algae in sediments. However, the release of nutrients from the sediment and the in situ control of CBs in lakes after PT should be further studied. Graphical abstract: Highlights: Plow-tillage was used to eliminate overwintering cyanobacteria for the first time. 10 cm or greater PT depth was favorable to eliminating overwintering cyanobacteria. The removal rate of viable cyanobacteria for 10-cm PT was 82.8%. The dark, anoxic environment after PT was responsible for death of cyanobacteria. The release of nutrients may increase due to cyanobacterial decomposition. Abstract : Plow-tillage at a depth of 10 cm or greater is an innovative and effective technique for eliminating viable, overwintering cyanobacteria in sediments.